2017
DOI: 10.1001/jamaoto.2016.3365
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Quality in Parents Considering Adenotonsillectomy or Tympanostomy Tube Insertion for Their Children

Abstract: Many parents experienced significant decisional conflict when making decisions about their child's elective surgical treatment. Parents who perceived themselves as being more involved in the decision-making process reported less decisional conflict and decisional regret. Future research should explore the influence of decision quality on health outcomes and develop methods to improve shared decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 36 publications
(100 reference statements)
3
57
0
Order By: Relevance
“…In the current study, 33.3% of parents had clinically significant decisional conflict. This is consistent with other studies assessing elective pediatric surgeries . Because tonsillectomy is one of the most commonly performed procedures in children in North America, the number of parents with significant uncertainty could be substantial.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, 33.3% of parents had clinically significant decisional conflict. This is consistent with other studies assessing elective pediatric surgeries . Because tonsillectomy is one of the most commonly performed procedures in children in North America, the number of parents with significant uncertainty could be substantial.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with other studies assessing elective pediatric surgeries. [21][22][23] Because tonsillectomy is one of the most commonly performed procedures in children in North America, the number of parents with significant uncertainty could be substantial. Consistent with previous studies conducted by our group, 22,23 a significantly negative correlation was found between the perceived level of parental SDM and decisional conflict.…”
Section: Discussionmentioning
confidence: 99%
“…This especially may be the case when parents have to make health decisions for their children. Parents can have high decisional conflict concerning surgical decision making for their children . See Table for definition of decisional conflict and other key terms.…”
Section: Discussionmentioning
confidence: 92%
“…Parents can have high decisional conflict concerning surgical decision making for their children. 28 See Table IV for definition of decisional conflict and other key terms. Increasing their knowledge and being informed allows them to decrease this conflict and anxiety to participate in the SDM process.…”
Section: Detection Of Complications*mentioning
confidence: 99%
“…Other research that evaluates parent-centered outcomes in pediatric tonsillectomy focus on outcomes such as disease-specific and health-related quality of life, parental knowledge about otolaryngologic disease and surgery, parent satisfaction with care, and parental decision conflict for surgery 5,3133 . Our study complements these previous studies by looking at parental experiences outside of the clinical context.…”
Section: Discussionmentioning
confidence: 99%